1979
DOI: 10.1207/s15328023top0604_9
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudinal Effects of Undergraduate Behavioral Training

Abstract: Students in a class, but not those in a practicum, became more accepting of behavior modification. Attitudes toward social learning were unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A client’s strengths would include past positive performances, abilities (Cormier & Cormier, 1985), past areas of success (Swenson, 1968), belief in the value of the recommendation, and knowledge about or specific interest in the behavior included in the recommendation that can be built on in counseling. Consultee knowledge about a recommendation has been found to increase the recommendation’s acceptability in consultation (Jeger & McClure, 1979; McMahon, Forehand, & Griest, 1981; Singh & Katz, 1985).…”
Section: Client Strengthsmentioning
confidence: 99%
“…A client’s strengths would include past positive performances, abilities (Cormier & Cormier, 1985), past areas of success (Swenson, 1968), belief in the value of the recommendation, and knowledge about or specific interest in the behavior included in the recommendation that can be built on in counseling. Consultee knowledge about a recommendation has been found to increase the recommendation’s acceptability in consultation (Jeger & McClure, 1979; McMahon, Forehand, & Griest, 1981; Singh & Katz, 1985).…”
Section: Client Strengthsmentioning
confidence: 99%
“…Several research teams (e.g., Jeger & McClure, 1979;McMahon, Forehand, & Griest, 1981) have suggested that more positive attitudes toward behavioral techniques follow increases in knowledge of such techniques. On the basis of this premise, McKee (1984) set out essentially to replicate Kazdin's (1980a) investigation of the acceptability of reinforcement of incompatible behavior, positive practice, timeout from reinforcement, and medication; his subjects were teachers whose knowledge of behavioral principles varied.…”
Section: Teachers' Treatment Preferences and Variables That Influence...mentioning
confidence: 99%
“…This represents the first such finding with this instrument. A previous study which employed this scale with college students undergoing either didactic or experiential training in behavior modification revealed no pre-post changes in either group (Jeger & McClure, 1979). It appears as though a combination of formal instruction and practical experience is necessary to induce change on this dimension.…”
Section: Results and D 1 S C U S S L O Nmentioning
confidence: 82%
“…The notion that attitudinal data of the kind obtained in the present study are sensitive to differing populations is further evident from the mean scores for subjects in this study. Even the experimental staff were in the medical model end of the continuum after training (i.e., a score of 52.55 compared to a theoretically neutral score of 60)' in contrast to students in the Jeger and McClure (1979) study who were already in the social learning direction prior to training. Since staff in the present study had been working with a traditional medical orientation for an average of almost ten years, the relative change obtained as a result of behavioral training is all the more meaningful.…”
Section: Results and D 1 S C U S S L O Nmentioning
confidence: 94%